Modulation of MCP-1, TGF-β1, and α-SMA Expressions in Granulation Tissue of Cutaneous Wounds Treated with Local Vitamin B Complex: An Experimental Study - Carla P. Martinelli-Kläy; Laurelucia O. Lunardi; Celso Ricardo Martinelli; Tommaso Lombardi; Edson G. Soares; Celso Martinelli (MDPI AG, 2014)
Vitamin B complex can modulate the inflammatory response and activate wound healing. However, the action mechanisms involved in this process are still unclear. The aim of this study was to evaluate the effects of vitamin B complex on the modulation of monocyte chemotactic protein (MCP)-1, transforming growth factor (TGF)-β1, and α-smooth muscle actin (α-SMA) in granulation tissue growth. Cutaneous ulcers on Wistar rats were topically treated with vitamin B complex. MCP-1, TGF-β1, and α-SMA expressions were evaluated 24, 72, and 168 h after the treatment. Inflammatory cells were counted and collagen fibril staining was performed. After 24 h, more mononuclear cells (p ≤ 0.01) and a higher MCP-1 (p ≤ 0.05) and TGF-β1 (p ≤ 0.01) expression were observed. After 72 h, the number of fibroblasts and mononuclear cells (p ≤ 0.05) was elevated. After 168 h, an increased number of fibroblasts, myofibroblasts, and blood vessels (p ≤ 0.01) as well as a strong intensity of collagen fibril staining were seen. At that point, the cells presented a higher TGF-β1 expression (p ≤ 0.05), and the size of the ulcer area was decreased (p ≤ 0.01). We can conclude that vitamin B complex may stimulate a positive modulation of MCP-1, TGF-β1, and α-SMA expressions in granulation tissue of cutaneous ulcers. © 2014 S. Karger AG, Basel